2020
DOI: 10.1038/s41598-020-77426-y
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-pot green synthesis of Ag–ZnO Nanocomposites using potato peeland their Ag concentration dependent photocatalytic properties

Abstract: Herein, a facile green synthesis route was reported for the synthesis of Ag–ZnO nanocomposites using potato residue by simple and cost effective combustion route and investigated the photocatalytic degradation of methylene blue (MB) dye. In the preparation potato extract functioned as a biogenic reducing as well as stabilizing agent for the reduction of Ag + , thus eliminating the need for conventional reducing/stabilizing agents. Ag–ZnO nanocomposites with different Ag mass fractions ranging from 2 to 10% wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(52 citation statements)
references
References 62 publications
4
48
0
Order By: Relevance
“…Characteristic peaks at 1 keV and 3 keV were observed for Zn and Ag, respectively. Lastly, all bimetallic Ag-ZnONPs were of high purity as their elemental composition was of O, Zn, and Ag only, as depicted in Figure 10A-D. Alharthi et al [45] reported on the incorporation of Ag into ZnO when Ag-ZnONPs were synthesized using potato peeland and characterized by EDX. EDX analysis of control and UV-C mediated ZnONPs shows the purity of ZnONPs synthesized by using M. macroura plant extract (Figure 9C,D).…”
Section: Energy Dispersive X-ray Analysismentioning
confidence: 95%
“…Characteristic peaks at 1 keV and 3 keV were observed for Zn and Ag, respectively. Lastly, all bimetallic Ag-ZnONPs were of high purity as their elemental composition was of O, Zn, and Ag only, as depicted in Figure 10A-D. Alharthi et al [45] reported on the incorporation of Ag into ZnO when Ag-ZnONPs were synthesized using potato peeland and characterized by EDX. EDX analysis of control and UV-C mediated ZnONPs shows the purity of ZnONPs synthesized by using M. macroura plant extract (Figure 9C,D).…”
Section: Energy Dispersive X-ray Analysismentioning
confidence: 95%
“…41–46 However, the segregation or formation of a local heterojunction 47 between Ag and ZnO does not result in any peak shift in XRD. 48,49 In fact, the formation of a local heterojunction, and interstitial and substitutional defects were dependent on the synthetic approach, cation hardness, and surfactant or/and solvent type. To indicate this, Yıldırım et al 42 showed an XRD pattern lower degree shift due to the substitution of Ag + into the ZnO lattice and a higher degree shift was shown by Modwi et al 46 due to the interstitial sites' doping.…”
Section: Dopant–host Reactivity Balancesmentioning
confidence: 99%
“…Comparable XPS binding energy shift and splitting values were also reported in the literature. 42,43,49,56,58–60 The lower energy shift is ascribed to the binding energy difference between Ag(0) and Ag( i ), in which Ag( i ) has much greater binding energy than Ag( i ).…”
Section: Dopant–host Reactivity Balancesmentioning
confidence: 99%
See 1 more Smart Citation
“…A recycle experiment was used to inspect the photostability of the photocatalyst, as reported in several studies [57][58][59]. The used ZnO-Cr 1 nanoparticles were centrifuged, washed and then dried for the next experiment.…”
Section: Study Of the Photocatalyst Stabilitymentioning
confidence: 99%